Field gamma-ray spectrometer GS256: measurements stability - MOJZEŠ, Andrej (Contributions to Geophysics and Geodesy, 2009)
The  stability of in  situ  readings of  the  portable gamma-ray spectrometer GS256 during  the ﬁeld season  of 2006 was  studied. The instrument is an impulse  detector  of gamma  rays  based  on NaI(Tl)  311 × 311  scintillation unit  and  256-channel  spectral analyzer which allows  simultaneous assessment of up to 8 radioisotopes in rocks.   It is commonly used  in surface geophysical survey for the measurement of natural 40 K, 238 U and 232 Th but  also  artiﬁcial 137 Cs quantities. The statistical evaluation is given  of both  repeated measurements - in the laboratory and  at  several ﬁeld  control  points  in  diﬀerent  survey areas.   The  variability of values shows both the instrument stability and also the relative inﬂuence  of some meteorological factors, mainly rainfalls.The analysis shows  an acceptable level  of instrument measurements stability, the necessity to avoid  measurement under  unfavourable  meteorological conditions and  to keep detailed ﬁeld book information about  time,  position  and  work conditions.